Challenges and prospects of 3D micro-supercapacitors for powering the internet of things. Issue 1 (25th October 2018) - Lethien, Christophe; Le Bideau, Jean; Brousse, Thierry
Abstract : The fabrication of miniaturized electrochemical energy storage systems is essential for the development of future electronic devices for Internet of Thing applications. This paper aims at reviewing the current micro-supercapacitor technologies and at defining the guidelines to produce high performance micro-devices with special focuses onto the 3D designs as well as the fabrication of solid state miniaturized devices to solve the packaging issue. Abstract : The fabrication of miniaturized electrochemical energy storage systems is essential for the development of future electronic devices for Internet of Things applications where connected devices are increasingly deployed in our daily life. On chip micro-supercapacitors are an attractive solution to fulfill the energy requirements of autonomous, smart, maintenance free and miniaturized sensors but they suffer from a limited energy density and poor technological readiness level in spite of high power capabilities and long cycle life. This paper aims at reviewing the current micro-supercapacitor technologies and at defining the guidelines to produce high performance micro-devices with special focus on 3D designs as well as the fabrication of solid state miniaturized devices to solve the packaging issue.